The Highway Rat - Donaldson, Julia; Scheffler, Axel (London : Alison Green Books, 2011)
A very bad rat rides his horse along the highway, stealing travelers' food, from a rabbit's clover to a spider's flies, until clever Duck introduces him to her "sister.".
2.4
K-3.
K-3
Keywords: Animals -- Juvenile fiction; Rats -- Juvenile fiction; Thieves -- Juvenile fiction; Animals -- Fiction; Rats -- Fiction; Robbers and outlaws -- Fiction; Stories in rhyme; Animals -- Fiction; Rats -- Fiction; Stories in rhyme; Thieves -- Fiction; Picture books for children